Funkcja i rola wysp jeziornych wedle przekazów pisanych dotyczących środkowoeuropejskich Słowian i Bałtów we wczesnym średniowieczu - Bartosz Tietz (Slavia Antiqua, 2022)
The text revolves around the use of lake isles by Western Slavs and Western Balts in the North European Plain in the early Middle Ages. The main goal of this article is to collect, discuss and analyse early medieval written sources that provide information about the locations’ forms and functions among old communities. This process has resulted in a picture of the various uses of isles by Slavs (and, to a small extent, by the Balts) which may serve as the starting point for an analysis of archaeological sources.